Assessing the Effect of Financial Literacy on Consumptive Behavior (Comparative Study Based on Gender) - Pamungkas, Mochamad Zidan; Firmialy, Sita Deliyana (APMBA (Asia Pacific Management and Business Application), 2023)
Financial literacy is the ability to comprehend one's financial management for actions such as transactions, use of financial services, etc., whereas consumptive behavior refers to one's activities in satisfying their needs and desires. This study aims to examine the relationship between digital-wallet users' financial literacy and their consumption patterns in online gaming transactions. This study also compares male gamers and female gamers (in total 126 respondents) levels of financial literacy and consumptive behavior.This study employs two quantitative method to answered the research questions, namely SEM-PLS method to answered the 1st-research questions, followed by the simple linear regression to answered the 2nd research questions. Based on the results of the bootstrapping analysis, financial literacy as an independent variable (X) can influence consumptive behavior, the dependent variable (Y). Furthermore, the study’s results indicate there are gender-specific differences in the level of financial literacy and consumptive behavior, whereas female gamers are more aware to their consumption level, rather than men gamers who are more prone to spending more excessively, in terms of buying.